Latin American credit ratings, the New Basel Capital Accord and portfolio risk - Theodore M. Barnhill; William C. Handorf (Economia Aplicada, 2002)
Commercial banks are required by regulation to maintain capital that varies with the perceived risk ofbanking assets. The risk-based capital rule initially introduced by the Bank for International Settlements in 1988 is under revision. This study provides an empirical analysis of proposed capital risk-weights for a sample of global assets. We apply a diffusion-based methodology for assessing the value-at-risk (VaR) of a portfolio offixedincome securities comparable to those now issued and likely to be issued for the foreseeable future by firms in Latin America. This is accomplished by simultaneously simulating both the future environment in which financial instruments will be valued and the credit rating of specific firms. This paper applies a simulation model to assess correlated market, basis and credit risk for both individual bonds and a portfolio ofbonds of similar initial credit quality. Interest rate or market risk is relatively more important for high-grade bonds issued by strong companies from developed countries. Basis risk and credit risk are more important for companies from countries whose sovereign debt is rated lower medium-grade and low-grade.